2002
DOI: 10.1002/path.1115
|View full text |Cite
|
Sign up to set email alerts
|

Progressive loss of PAX9 expression correlates with increasing malignancy of dysplastic and cancerous epithelium of the human oesophagus

Abstract: Pax genes encode a family of transcription factors that play key roles in embryonic development. Whereas the functions of Pax genes in the adult organism are largely unknown, upregulated Pax gene expression has been implicated in tumourigenesis. In this study, PAX9-specific monoclonal antibodies have been generated and it has been shown that PAX9 protein is expressed in the normal epithelium of the adult human oesophagus. PAX9 expression was either lost or significantly reduced in the majority of invasive carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 22 publications
(19 reference statements)
5
56
0
Order By: Relevance
“…Embryos were staged by taking mid-day on the day of vaginal plug detection as embryonic day 0.5 (E0.5). Embryonal heads were embedded in paraffin wax, sectioned, stained with a monoclonal anti-Pax9 antibody, and documented as previously described (Gerber et al, 2002;Kist et al, 2005). Staining of cartilage and bone was performed with alcian blue and alizarin red as described (Kessel et al, 1990).…”
Section: Phenotype Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Embryos were staged by taking mid-day on the day of vaginal plug detection as embryonic day 0.5 (E0.5). Embryonal heads were embedded in paraffin wax, sectioned, stained with a monoclonal anti-Pax9 antibody, and documented as previously described (Gerber et al, 2002;Kist et al, 2005). Staining of cartilage and bone was performed with alcian blue and alizarin red as described (Kessel et al, 1990).…”
Section: Phenotype Analysismentioning
confidence: 99%
“…A role for Pax9 in epithelial differentiation has been suggested by a study showing that maintenance of PAX9 protein expression in epithelial dysplasia and squamous cell carcinoma of the human esophagus appears to be associated with a favorable outcome (Gerber et al, 2002). However, since Pax9-deficient mice die shortly after birth, the function of Pax9 during late phases of organ development and in tissue homeostasis at postnatal stages is not known.…”
mentioning
confidence: 96%
“…The role of Pax9 in epithelial differentiation was suggested in a study which showed that the maintenance of Pax9 protein expression in epithelial dysplasia and squamous cell carcinoma of the human esophagus, appears to be associated with a favorable outcome. 12 However, since Pax9-deficient mice die shortly after birth, the function of Pax9 during the late phases of organ development and in tissue homeostasis in the postnatal stages is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Human Esophagus *Keratinocytes Normal differentiation process of internal stratified squamous epithelia (esophageal keratinocytes) -increasing malignancy of dysplasias is associated with a progressive loss of PAX9 expression (Gerber et al, 2002) Human Mouse Esophagus Not specified (RNA)** Formation and maintenance of internal stratified squamous epithelium in the anterior digestive tract, which is a different epithelial type to the caudal digestive tract (simple monolayered epithelium) (Peters et al, 1997) Anterior digestive tract *Tongue, oral epithelium, salivary gland, pharynx, esophagus Thymus Not specified (RNA)** Not specified (Neubuser et al, 1995) a Unless indicated analysis indicates in vivo expression in adult differentiated cells and not cell lines or progenitor cells of adult tissue. GWGP, German Waltzing guinea pig.…”
Section: Pax9mentioning
confidence: 99%